Wastewater Treatment Using Environment Friendly Technology (International Journal of Innovative Research in Engineering & Management, 2021)
The increasing water supply challenges have become a  significant problem; as severe water shortages have been seen  worldwide. While the MBR has made great development and  has shown to be a viable option for waste water treatment,  conventional MBRs still have numerous weaknesses, which is  why the MBRs for waste water processing technologies have  been incorporated. This article aims to combine the current  state of the art for the integrated MBR process with other  wastewater treatment systems and offer a consolidated  analysis of the sustainability of the treatment process. This  article looks at the potential applications of various types of  MBR. It aims to prepare the path for the future deployment of  improved MBR as a potential wastewater treatment  technology. The improvement in wastewater in integrated  MBR will reduce emissions and provide a new energy and  nutrient source. The improved MBR also enables the recovery  of energy and nutrients ecologically and economically  feasible.
Keywords: AnMBR; Green Technology; MBR; Membrane Bioreactor; Wastewater Treatment